DEVELOPING LINGUISTIC SKILLS IN ENGLISH TEACHING STUDENTS THROUGH ENGLISH LITERATURE AND THEIR CULTURAL UNDERSTANDING (International Journal of Food and Nutritional Sciences, 2022)
Literature; in addition, being considered an art, it is also a component in the training of a professional in teaching the English language. Furthermore, in a deeper analysis, it can be deduced that the English language teaching professional should know English literature and the origin of the English language, taking into account aspects related to Linguistics. However, the curriculum of the English teaching career at UAM (Universidad Americana de Costa Rica) has courses of Literature developed in Poetry, Narrative, and Drama and they analyzed important details in the evolution of the English literature, culture, language, history and linguistics; nevertheless, are the students well prepared to teach literature? Do they know what specific techniques, methods or approaches for teaching Literature? These aspects of the study are considered part of an investigation that aims to expose not only the theory but also recommend future English teachers in the teaching of English literature.